Modality in Modern Greek - Staraki, Eleni (Cambridge Scholars Publishing, 2017)
This book provides a formal analysis of both main and embedded modality in the modern Greek language. By reassessing the main arguments of the classical semantic and syntactic literature related to modality, this study offers a new account of its interpretation in modern Greek in terms of non-veridicality and non-monotonic principles. It is argued that the interpretation of modality in modern Greek depends on semantic and discourse components which are regulated by contextual information, evidentiality, causation, and inference. The analysis offered implies a greater significance of modality, the components of which can be distinguished in the incorporation of the inferential model of an individual.